Effect of generator temperature on steam ejector performance in renewable refrigeration cycle considering wet steam model and dry steam model - Jiang, Jian; Yin, Yanping (International Journal of Renewable Energy Development, 2024)
The rise in global warming has led to an increased utilization of cooling systems. High energy consumption associated with common refrigeration cycles not only contributes to air pollution but also intensifies the consumption of fossil fuels. Consequently, the imperative to conserve energy has become paramount in today's world. One of the methods to decrease energy consumption involves employing systems capable of harnessing waste heat from industries, solar energy, and other sources. The ejector refrigeration cycle (ERC) stands as an example of such systems. In present study, the impact of elevating the generator temperature on various aspects such as flow behavior in the ejector, aerodynamic shocks, entrainment ratio (ER), and entropy production was examined. The investigation encompassed both wet steam model (WSM) and dry steam model (DSM). Based on the findings, it was observed that with an increase in generator temperature, the ER decreases while the production entropy increases. In the WSM, the liquid mass fraction (LMF) also experiences an increase. Additionally, the Mach number distribution in the DSM surpasses that of the WSM and the temperature drop in the DSM is greater compared to the WSM. With the rise in generator temperature from 388 K to 418 K, both the DSM and WSM exhibit a decrease in ER by 52.9% and 58.7%, respectively. Furthermore, the production entropy experiences a substantial increase of 180% and 206% for the DSM and WSM, respectively.